Factors influencing clients' choice of standard form construction contracts: a case study of three metropolitan municipalities in South Africa - Ndlovu, Hosana Hossain (My University, 2017)
In the public sector, the decision as to which form of construction contract to select, remains a challenging and difficult task for many clients of construction projects. Selecting the most appropriate form of construction contract is one of many important decisions that a client has to make in a project, and such a decision may lead to project success. The factors that influence clients to make selections of construction contracts are not clearly understood. There is a lack of distinction or structured guidelines as to how forms of construction contracts are to be selected or by what process; however there are consequences for selecting inappropriate forms of construction contracts. The aim of this study was to determine the factors that influence clients’ choice of forms of construction contracts when implementing construction projects. Through the use of qualitative research methodology, a case-study of the three metropolitan municipalities in the South African Province of Gauteng; namely, the City of Tshwane, the City of Johannesburg and Ekurhuleni Metropolitan Municipality was conducted. The study population consisted of built environment professionals (engineers, architects, project managers, programme managers, construction managers and investment managers). Data was collected through structured interviews with specific questions relating to how forms of construction contracts are selected, what factors influence such choices and who the key drivers of such contract selection decisions are. The results have shown that the leading factors, according to respondents, that influence clients to select the forms of construction contracts they use for their projects are the influence of their consultant and familiarity. The suitability of forms of construction contracts was the least factor. The study further demonstrates that the most commonly used form of construction contract in the three metropolitan municipalities is the General Conditions of Contract (GCC 2010/2015) and the key drivers of such decisions are consultants, who are seen as the experts. It is recommended that clients need to be more involved in all construction management processes and rely less on consultants. The outcome of this research will help the industry to best deal with the problem of random selection of forms of construction contracts without proper analysis.
A research report submitted n partial fulfillment for the requirements for the degree of Master of Science in Building (Project Management in Construction) to the Faculty of Engineering and Built Environment, in the School of Construction Economics and Management, University of the Witwatersrand, Johannesburg, 2017.
Keywords: Construction contracts--South Africa; Construction industry